Enhancing Student Preparedness Through Disaster Simulation On Campus - Saputra, Andi; Novalia, Vera; Utariningsih, Wheny; Zara, Noviana (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This community service program aims to enhance student preparedness in facing disasters through the implementation of disaster simulations on campus. In an era marked by the increasing frequency and intensity of natural disasters, it is crucial for students as the younger generation to possess adequate knowledge and skills related to disaster mitigation and response. The methods used in this program include theoretical education, practical training, and disaster simulation involving realistic scenarios. The results of the program indicate a significant improvement in students' knowledge, skills, and awareness regarding disasters. The simulation also strengthens coordination among students, faculty, and other stakeholders in handling emergency situations. Thus, this program makes a tangible contribution to creating a disaster-resilient campus environment.